Eu and dy co-activated SrB2Si2O8 blue emitting phosphor: synthesis and luminescence characteristics - Leow, T.Q.; Hussin, R.; Ibrahim, Z.; Deraman, K.; Shamsuri, W.N.W.; Lintang, H.O. (Universiti Kebangsaan Malaysia, 2015)
The main focus in this research was to understand the influence of Dy3+ and Eu3+ doping/co-doping and sintering atmosphere on the luminescence properties of SrB2Si2O8. Single phase Eu and Dy doped/co-doped SrB2Si2O8 ceramics were synthesized in different atmosphere through solid state reaction technique. An inexpensive method was occupied to provide reducing sintering atmosphere. Europium doped SrB2Si2O8 exhibit unusual reduction from trivalent to a divalent oxidation state even in an oxidizing atmosphere. We also discovered co-doping with Dy3+ ions produced further europium reduction in this phosphor. By manipulating the sintering condition and co-doping, a reddish-purple to blue tune-able phosphor under 390 nm excitations were produced and their Commission International del’Eclairage (CIE) color coordination were calculated and plotted in a CIE 1931 diagram. Photoluminescence spectra of the Eu2+/Eu3+ and Dy3+ co-doped SrB2Si2O8 phosphor showed energy transfer from Dy3+ to Eu3+ and Eu2+ which was observable in Dy3+ f-f excitation transitions and the Dy-O charge transfer bands. A weak 777 nm emission from 3p5P to 3s5S0 transition of O2- ions were observed in all the samples. The excitation and emission peaks of f - f transition from Dy3+ and Eu3+ as well as 4f - 5d transition of Eu2+ were also discussed. The long excitation band in ultraviolet (UV) region from these doped/co-doped SrB2Si2O8 ceramics produced phosphors with efficient UV excitation for solid state lighting.